Counseling and Training on Mediation in Family Disputes as an Alternative to Dispute Resolution for Members of The Muhammadiyah Branch Leadership (PCM) Ulujami, Pemalang District - Zeehan Fuad Attamimi; Luthfi Kalbu Adi; Tesa Nurul Hidayah (Proceedings Series on Social Sciences & Humanities, 2023)
Community service activities carried out by a team from the Faculty of Law, Muhammadiyah Purwokerto University which was held on February 3, 2023, located in Ulujami District, Pemalang Regency. The implementation of counseling activities and mediation training is one way to prevent divorce. Based on statistical data that Pemalang Regency is the district with the second highest divorce rate in Central Java. Both divorces are caused by divorce that is done by the husband or divorce that is done by the wife. There are factors that cause divorce filed at the Pemalang Religious Court. The purpose of this service, to reduce the divorce rate in Pemalang Regency, especially for members of the Muhammadiyah Branch Leadership (PCM) Ulujami with the need for counseling and mediation training as an effort to prevent the breakdown of marriage due to divorce if one of the two husbands and wives sues for divorce, and between husband and wife can get along again to become a complete family. Thus conducting counseling and mediation training as an alternative to family dispute resolution is very necessary for districts / cities with high divorce rates. Some of the supporting factors for this service activity include the very high enthusiasm of the members to gain knowledge and training with the presence of 35 members from each family representative under PCM Ulujami Pemalang Regency. Some of the obstacles faced during the service were limitations in supporting facilities including limited space and limited time.